Hydiorhythmia. Tracing the circle - Ceriani , Giulia (E|C, 2024)
We propose a reflection about the value driven by the concept of idiorhythmy, and on how it questions both the notion of difference and that of uniqueness: we try to probe the paradox of a rejected sociality yet incorporated into its contradictions, where the rhythmic structure itself regenerates the modes of identification and adhesion. More specifically, we deal with the reversal and regeneration of the criteria of “happy” sociality, challenging the conventional folds of meaning. In this sense, idiorhythmy becomes a sort of provocative paradigm of the contemporary and its media dialectics, poised between the solitude of the substitute relationship (via deepfake, avatar, prosthesis or more simply abandonment to remote dialogue/performance) and the need of an audience that configures the recipient as a present/absent figure. It is the theme of the “right” distance, of the circle that asks us to identify the limit, and of the mobile thresholds of the limit itself.